Perspektywa teorii Pierre’a Bourdieu w polskich badaniach socjologicznych - Dębska, Katarzyna (Studia Socjologiczno-Polityczne. Seria Nowa, 2016)
Theory of Pierre Bourdieu has already gained an undisputed status in Polish sociology. This text is an attempt to show the diversity of ways of using the theory of Bourdieu by Polish scholars and researchers. The author identifies areas in which Bourdieu’s theory is used in Polish research. These are: study of social class analysis fields (fields of literature, music, contemporary art and legal and advertising fields), diagnosis of social inequalities in education and other areas of life, analysis of functioning of elites and the various types of capitals in the Polish socio-economic context. The text indicates tensions occurring between approaches and interpretations thoughts Bourdieu, represented by Polish researchers. The author also points out opportunities of developing research concepts inspired by Pierre Bourdieu, which would take into account such dimensions of social diversity as gender or sexual orientation.